Tapping the Economic Potential of Chickpea in Sub-Saharan Africa - Asnake Fikre; Haile Desmae; Seid Ahmed (Agronomy, 2020)
Chickpea is a nutrition-rich, cropping-system friendly, climate-resilient, and low-cost production crop. It has large economic potential in the sub-Saharan Africa (SSA) region, where it currently accounts for only approximately half a million hectares of the approximately 12 million hectares of total chickpea production land worldwide. This review highlights the opportunities for promoting chickpea production and marketing to tap the vast economic potential in SSA. The region can potentially produce chickpea on approximately 10 million hectares, possibly doubling the global production, and the region could become one of the highest consumption geographies of this healthy crop. Chickpea could easily be integrated into existing cropping systems including rice-fallows and cereal monocropping systems. Successful cases studies of the crop in the region are highlighted. The region could tap into the potential at scale through intervention in the agricultural policy environment and development and promotion of improved chickpea production technologies supported by well-organized extension services and sustainable seed systems. These interventions could be complemented with value addition and product quality improvementsÍ for SSA chickpea to benefit from high-value markets.